2019
DOI: 10.1007/s13524-019-00772-8
|View full text |Cite
|
Sign up to set email alerts
|

Shared Lifetimes, Multigenerational Exposure, and Educational Mobility

Abstract: In this article, we report analyses of the effects of fertility and mortality trends on the mutual exposure of grandparents and grandchildren and their consequences for multigenerational processes of social mobility in the United States from 1900 to 2010. Using historical vital statistics and stable population models, we report systematic analyses of grandparent-grandchild exposures from both prospective (grandparent) and retrospective (grandchild) perspectives. We also estimate exposure levels and trends spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Ignoring parents' and offspring' life cycles in the estimation of intergenerational association may lead to "life-cycle bias" (Mazumder 2005;Haider and Solon 2006). Furthermore, shared lifetimes, namely years during which two or more generations overlap, often vary across families and may predict the cumulative amount of influence from one generation to another (Song and Mare 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Ignoring parents' and offspring' life cycles in the estimation of intergenerational association may lead to "life-cycle bias" (Mazumder 2005;Haider and Solon 2006). Furthermore, shared lifetimes, namely years during which two or more generations overlap, often vary across families and may predict the cumulative amount of influence from one generation to another (Song and Mare 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A number of social demographic studies have reported that the prevalence and relevance of grandparenthood are increasing, as growing numbers of grandparents are taking on more active roles in raising their grandchildren (Fuller-Thomson, 2005;Kopera-Frye, 2009;Hayslip, Fruhauf, & Dolbin-MacNab, 2019). The availability of grandparents, and especially of maternal grandmothers, can improve the survival of children (Sear & Mace, 2008;Sear & Coall, 2011), and their educational attainment (Song & Mare, 2019). However, it has been argued that caring for grandchildren can negatively affect the physical and mental health and general well-being of grandparents (Neely- Barnes, Carolyn Graff, & Washington, 2010;Musil et al, 2011).…”
Section: The Double Burden Of Care and Workmentioning
confidence: 99%
“…Existing studies on this topic have noted that the overlap between grandparents and grandchildren is expected to increase in countries of the Global North (Margolis & Verdery, 2019;Margolis & Wright, 2017;Song & Mare, 2019). To the best of our knowledge, no study to date has estimated the global prevalence of grandsandwichness.…”
Section: Sandwichness As An Intergenerational Demographic Processmentioning
confidence: 99%
“…Kinship networks provide pathways for all kinds of intergenerational support. Parentchild and grandparent-grandchild interactions are obviously important; Song and Mare (2019) have emphasized the importance of multigenerational exposures. On a larger scale, Kramer (2019) argues that the human life history, characterized by earlier wean-ing and shorter birth intervals than is the case in other primates, results in larger kinship groups and that the resulting inter-generational support and transfer of resources among relatives has played a major role in the demographic success of humans as a species.…”
Section: Introductionmentioning
confidence: 99%